Assessing general versus specific liability for externalizing problems in adolescence: concurrent and prospective prediction of symptoms of conduct disorder, ADHD, and substance use - Perkins, Emily; Joyner, Keanan J.; Foell, Jens; Drislane, Laura E.; Brislin, Sarah J.; Frick, Paul J.; Yancey, James R.; Soto, Elia F.; Ganley, Colleen M.; Keel, Pamela K.; Sica, Claudio; Flor, Herta; et al. (Journal of psychopathology and clinical science, 2022)
This study explored the generality versus specificity of two trait-liability factors for externalizing problems—disinhibition and callousness—in the concurrent and prospective prediction of symptoms of conduct disorder, attention-deficit/hyperactivity disorder (ADHD), and substance use (i.e., alcohol use disorder and history of illicit substance use). Disinhibition involves an impulsive, unrestrained cognitive-behavioral style; callousness entails a dispositional lack of social-emotional sensitivity. Participants were European adolescents from the multisite IMAGEN project who completed questionnaires and clinical interviews at ages 14 (N = 1,504, Mage = 14.41, 51.13% female) and 16 (N = 1,407, Mage = 16.46, 51.88% female). Disinhibition was related concurrently and prospectively to greater symptoms of conduct disorder, ADHD, and alcohol use disorder; higher scores on a general externalizing factor; and greater likelihood of having tried an illicit substance. Callousness was selectively related to greater conduct disorder symptoms. These findings indicate disinhibition confers broad liability for externalizing spectrum disorders, perhaps due to its affiliated deficits in executive function. In contrast, callousness appears to represent more specific liability for antagonistic (aggressive/exploitative) forms of externalizing, as exemplified by antisocial behavior. Results support the utility of developmental-ontogenetic and hierarchical-dimensional models of psychopathology and have important implications for early assessment of risk for externalizing problems. (PsycInfo Database Record (c) 2022 APA, all rights reserved)